Development of a 5′ Nuclease-Based Real-Time PCR Assay for Quantitative Detection of Cariogenic Dental Pathogens Streptococcus mutans and Streptococcus sobrinus - Yoshida, Akihiro (American Society for Microbiology, 2003)
A 5′ nuclease TaqMan PCR assay was developed for the quantitative detection of the major cariogenic bacteria Streptococcus mutans and Streptococcus sobrinus. The absolute and relative numbers of bacteria were measured by this method. This assay will be useful for quantifying these organisms in oral specimens and for analyzing biofilm formation.